A test of stress, cues, and re-exposure to large wins as potential reinstaters of suboptimal decision making in rats - Connolly, Nina P.; Kim, Jung S.; Tunstall, Brendan J.; Kearns, David N. (Frontiers in Psychology, 2015)
The present experiment investigated potential reinstaters of suboptimal economic decision making in rats. Rats were first trained on a version of the rat Gambling Task under conditions designed to promote choice of a suboptimal option that occasionally resulted in large “wins” (4 sucrose pellets). In a second phase, preference for this economically suboptimal option was reduced by substantially increasing the probability of punishment when this option was chosen. Then, three events were tested for their ability to reinstate choice of the suboptimal option. A brief period of re-exposure to a high frequency of large wins significantly increased choice of the suboptimal option. The pharmacological stressor yohimbine did not reinstate suboptimal choice, but did increase impulsive action as indexed by premature responding. Presentation of cues previously associated with large wins did not alter behavior. Results suggest reinstaters of suboptimal choice may differ from reinstaters of extinguished drug- and food-seeking behavior.